General characteristics of depression syndrome - Ravshanova Inoyat Erkinovna; DJuraeva Nasibakhon Mirzohijon kizi (Genius Journals, 2025)
This article provides information about the occurrence of depression syndrome, its causes, risk factors, manifestations and classification by the development of the syndrome.
Keywords: biological; thinking; conflict